h - Cohen, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 21 International Conference on Database and Expert Systems Applications, DEXA 2010, held in Bilbao, Spain, August 30-September 3, 2010. The 45 revised full papers and 36 short papers were carefully reviewed and selected from197 submissions. The papers are organized in topical sections on Web, Semanics and Ontologies, Information Integration and Process Modelling, Streams and Multimedia Databases, Data Management Algorithms and Performance, Decision Support Systems and Performance, Data Streams, XML Databases, Programming Language and Cooperative Work, Query processing and Optimization, Data Privacy and Security, Temporal, Spatial, and High Dimensions Databases, Semantic Web and Ontologies.
Invited Talks -- SAT Modulo Theories: Getting the Best of SAT and Global Constraint Filtering -- Constraint-Directed Search in Computational Finance and Economics -- Constraints, Graphs, Algebra, Logic, and Complexity -- Distinguished Papers -- Testing Expressibility Is Hard -- Applying Constraint Programming to Identification and Assignment of Service Professionals -- Computing the Density of States of Boolean Formulas -- Research Track -- Towards Parallel Non Serial Dynamic Programming for Solving Hard Weighted CSP -- Making Adaptive an Interval Constraint Propagation Algorithm Exploiting Monotonicity -- Improving the Performance of maxRPC -- Checking-Up on Branch-and-Check -- Spatial, Temporal, and Hybrid Decompositions for Large-Scale Vehicle Routing with Time Windows -- Decomposition of the NValue Constraint -- Propagating the Bin Packing Constraint Using Linear Programming -- Sweeping with Continuous Domains -- A New Hybrid Tractable Class of Soft Constraint Problems -- A Propagator for Maximum Weight String Alignment with Arbitrary Pairwise Dependencies -- Using Learnt Clauses in maxsat -- Domain Consistency with Forbidden Values -- Generating Special-Purpose Stateless Propagators for Arbitrary Constraints -- Including Ordinary Differential Equations Based Constraints in the Standard CP Framework -- Structural Tractability of Enumerating CSP Solutions -- Diversification and Intensification in Parallel SAT Solving -- A Systematic Approach to MDD-Based Constraint Programming -- A Complete Multi-valued SAT Solver -- Exact Cover via Satisfiability: An Empirical Study -- On the Complexity and Completeness of Static Constraints for Breaking Row and Column Symmetry -- Ensemble Classification for Constraint Solver Configuration -- On Testing Constraint Programs -- On the Containment of Forbidden Patterns Problems -- Improving the Floating Point Addition and Subtraction Constraints -- The Lattice Structure of Sets of Surjective Hyper-Operations -- Constraint Based Scheduling to Deal with Uncertain Durations and Self-Timed Execution -- Local Consistency and SAT-Solvers -- Heuristics for Planning with SAT -- Value-Ordering Heuristics: Search Performance vs. Solution Diversity -- A New Not-First/Not-Last Pruning Algorithm for Cumulative Resource Constraints -- A Generic Visualization Platform for CP -- Database Constraints and Homomorphism Dualities -- A Box-Consistency Contractor Based on Extremal Functions -- Exponential Propagation for Set Variables -- Applications Track -- An Empirical Study of Optimization for Maximizing Diffusion in Networks -- An Integrated Modelling, Debugging, and Visualisation Environment for G12 -- Global Constraints on Feature Models -- Constraint Programming for Mining n-ary Patterns -- An Integrated Business Rules and Constraints Approach to Data Centre Capacity Management -- Context-Sensitive Call Control Using Constraints and Rules -- Load Balancing and Almost Symmetries for RAMBO Quorum Hosting -- Testing Continuous Double Auctions with a Constraint-Based Oracle -- A Safe and Flexible CP-Based Approach for Velocity Tuning Problems -- Contingency Plans for Air Traffic Management.
Keywords: Computer science; Computer software; Logic design; Artificial intelligence; Computer Science; Algorithm Analysis and Problem Complexity; Mathematical Logic and Formal Languages; Logics and Meanings of Programs; Artificial Intelligence (incl. Robotics).; Programming Languages, Compilers, Interpreters; Computation by Abstract Devices